(untitled) (Historia, 2021)
As the burgher population at the Cape of Good Hope developed over the course of the eighteenth century, identity and status became increasingly important. Material culture, used for the purpose of personal adornment, was a prominent means of demonstrating social positions. This article explores the role of burgher women in Cape Dutch society, and demonstrates how this group used clothing as markers of distinction to denote their social position. By using objects such as clothing, free burgher women managed to create an association with a particular status group, and in so doing increased their own social importance. Association with the higher echelons of society was particularly important to a group of nouveaux riche burghers who had started to intermarry with the VOC official elite. This article argues that burgher women in perpetuating the notion of “conspicuous consumption” used clothing and personal adornment as a means of establishing and in some instances increasing their status and social importance in Cape Dutch society.